The role of gut microbiota in autoimmune disease progression and therapy: a comprehensive synthesis - Adawi, Mohammad (Frontiers in Microbiomes, 2025)
Autoimmune diseases arise from the immune system’s dysregulated attack on the body’s own tissues, influenced by a complex interplay of genetics, environment, and the microbiome. This comprehensive review and meta-analysis examines the dynamic relationship between gut microbiota and autoimmune diseases, highlighting their role in disease onset, progression, and potential therapeutic interventions. Emerging evidence underscores the bidirectional interactions between microbiota and immune pathways, particularly through mechanisms like mucosal immune modulation and regulatory T-cell activity. Microbiota dysbiosis, characterized by altered diversity and function, is consistently associated with autoimmune conditions such as rheumatoid arthritis, multiple sclerosis, and type 1 diabetes. The review identifies critical microbiota-driven factors, including antigenic mimicry and inflammatory signaling pathways that disrupt immune tolerance and exacerbate autoimmunity. Meta-analysis findings reveal a consistent reduction in microbial diversity across autoimmune diseases, emphasizing the role of specific taxa and their metabolites in influencing disease severity and immune responses. Therapeutic strategies, such as probiotics, prebiotics, and microbiome-targeted interventions, offer promising avenues to restore microbiome balance and mitigate autoimmune inflammation. Despite significant advances, challenges in methodology, limited longitudinal studies, and heterogeneity in results highlight the need for standardized research protocols and larger, well-controlled clinical trials. Future studies should prioritize personalized approaches to microbiome modulation, integrating dietary, genetic, and environmental factors to improve disease management and prevention. This work consolidates current knowledge, providing a framework for future research and clinical applications in the field of microbiome-autoimmune interactions.